Growth and characterisation of titanium sulphide nanostructures by surface–assisted vapour transport methods; from trisulphide ribbons to disulphide nanosheets. (10th January 2012) - Denholme, S.J.; Dobson, P.S.; Weaver, J.M.R.; MacLaren, I.; Gregory, D.H.
Surface Assisted Chemical Vapour Transport (SACVT) methods have been employed to grow nanostructures of titanium disulphide (TiS2 ) and titanium trisulphide (TiS3 ). SACVT reactions occur between titanium and sulphur powders to form TiSx species transported in the vapour phase to grow nanometric flower–like structures on titanium–coated silica substrates. The evolution of structure and composition has been followed by powder X–ray diffraction, electron microscopy and Raman spectroscopy. At 1 : 2 Ti : S ratios, the size and shape of the hexagonal 1T–TiS2 titanium disulphide structures formed can be varied from flower–like growths with 'petals' formed from nanosheets 10 nm thick to platelets microns across. Increasing the proportion of sulphur (Ti : S 1 : 4) enables TiS3 flower–like structures composed of radiating nanoribbons to grow at elevated temperatures without decomposition to TiS2 . TEM/SAED suggests that individual trisulphide ribbons grow along the [010] direction. Magnetic properties of the disulphide nanomaterials have been determined using SQUID magnetometry and Raman spectra for disulphides suggest that their crystal and electronic structures may be more complex than expected for bulk, stoichiometric, CdI2 –structured TiS2 .